KONSEPTUALISASI HUKUM DALAM PENINGKATAN KUALITAS PENDIDIKAN AGAMA ISLAM DI INDONESIA - Sanata, Kalen; Ramadoni, Sofwan Rizko; Gegana, Reza Pramasta (Langgong: Jurnal Ilmu Sosial dan Humaniora, 2023)
The issue of education and religion is a fundamental issue and is always an issue of discussion among academics and practitioners. The role of parents at home, teachers at school, and lecturers at campus is considered to be the biggest reason that influences the level of education and spirituality in Indonesia. Various approaches have been used to analyze why the level of education in Indonesia is still one of the worst in Asian countries. Even though our constitution clearly states that one of the duties of the state is to make the nation's life intelligent. The importance of education with character as initial capital to live a true life is found in the family environment, school and campus. In this case, the formation of educational character does not only rely on general knowledge, but must be balanced with spiritual knowledge. This article uses a doctrinal research method, namely the author collects material from literature, both hardcopy and softcopy, related to the title of this research using an analysis of the research object. This article focuses on discussing how the Islamic Religious Education Governance system is in Indonesia and the role of law in improving the quality of Islamic Religious education in Indonesia. Because in Islam, one of the best people is one who is able to produce a quality generation with knowledge and spirituality that reflects the Koran and Sunnah of Rasullullah Shallallahu 'Alaihi wa Sallam.